Evaluation of the in vitro antiplasmodial and toxicity profiles of novel drug delivery formulations for combination therapies - Birkholtz, Lyn-Marie (University of Pretoria, 2025)
Dissertation (MSc (Biochemistry))--University of Pretoria, 2024.